أثر السياحة في بيئة الساحل السوري وطرق حمايتها - خضرة, جلال (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتعرض المجمع الطبيعي في المنطقة الغربية من الجمهورية العربية السورية لتأثيرات الأنشطة البشرية وذلك نتيجة للفعالية الزائدة للنشاط البشري أو للتوسع في استثمار الأرض من أجل السياحة والاستجمام، هذا يتطلب منا حماية المناطق الطبيعية لاسيما العذراء منها والحفاظ عليها والتي تمثل قيمة خاصة للبشرية. وذلك للحيلولة دون تدهور البيئة الطبيعية، تركز هذه الدراسة على دراسة الواقع السياحي القائم وذلك لوضع استراتيجية مستقبلية لاستثمار هذا المجمع الطبيعي يراعي فيهما الحفاظ على الموارد السياحية المتاحة وتحديد قدرتها على تلبية المتطلبات السياحية، ومقدرتها على الحمولات السياحية وتحديد البيئة الطبيعية، والإقليمية للمنطقة الغربية من القطر. The western part of the Syrian Arab Republic is exposed to the negative effects of human activities in the natural environment due to increased human activities or expansion in the exploitation of land for recreation and tourism. Therefore, masseurs are required to protect and preserve the natural areas, especially the virgin ones, because of their value for human beings. In order to do that, this study focuses on examination of the current status so as a future strategy can be devised for the exploitation of the natural environment in a way that meets the requirements of tourism without negatively nature in the western part of Syria.